EXPERIMENTAL STUDY ON BAMBOO AS REINFORCED CONCRETE AND COMPARE THE STRENGTH, DURABILITY OF CONVENTIONAL CLAY BRICKS WITH LIGHT WEIGHT INTERLOCKING BRICKS - Prafulla Subhash Kamble (International Journal of Innovations in Engineering Research and Technology, 2022)
Our aim through this project is to find a suitable Eco-friendly material that replaces present conventional materials which are in demand or in the path of demand [1-3]. A suitable material that can replace steel in construction field is Bamboo Through this paper, we are going to study and analyses about the utilization of Bamboo in construction field such as Reinforcement purposes, for structural elements, Bamboo constructions[4-5], etc.